2/3 + 5/6 - 1/2

asked by guest
on Mar 25, 2025 at 6:46 pm



You asked:

Evaluate the expression: 23+5612\frac{2}{3} + \frac{5}{6} - \frac{1}{2}

MathBot Answer:

23+5612=1 \frac{2}{3} + \frac{5}{6} - \frac{1}{2} = 1


The sum can be computed by rewriting each term over a common denominator, where the least common denominator of 23\frac{2}{3}, 56\frac{5}{6}, and 12\frac{-1}{2} is 66. 23+5612=2232+5161+1323=4+5+36=66=1 \begin{aligned} \frac{2}{3} + \frac{5}{6} - \frac{1}{2} &= \frac{2 \cdot 2}{3 \cdot 2} + \frac{5 \cdot 1}{6 \cdot 1} + \frac{-1 \cdot 3}{2 \cdot 3} \\ &= \frac{4 + 5 + -3}{6} \\ &= \frac{6}{6} \\&= 1 \end{aligned}